2019
DOI: 10.1101/727743
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indirect actuation reduces flight power requirements inManduca sextavia elastic energy exchange

Abstract: In the vast majority of flying insects, wing movements are generated indirectly via the deformations of the exoskeleton. Indirect measurements of inertial and aerodynamic power requirements suggest that elastic energy exchange in spring-like structures may reduce the high power requirements of flight by recovering energy from one wingstroke to the next. We directly measured deformation mechanics and elastic energy storage in a hawkmoth Manduca sexta thorax by recording the force required to deform the thorax o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(57 citation statements)
references
References 46 publications
5
52
0
Order By: Relevance
“…This is consistent with evidence that elastic energy exchange substantially reduces the power requirements of insect flight [3,4,5,6,7,8]. As the wing decelerates, elastic elements store excess kinetic energy and subsequently return this energy to reaccelerate the wing.…”
Section: Resonant Systems Cannot Escape Tradeoffs Between Energy and supporting
confidence: 86%
See 3 more Smart Citations
“…This is consistent with evidence that elastic energy exchange substantially reduces the power requirements of insect flight [3,4,5,6,7,8]. As the wing decelerates, elastic elements store excess kinetic energy and subsequently return this energy to reaccelerate the wing.…”
Section: Resonant Systems Cannot Escape Tradeoffs Between Energy and supporting
confidence: 86%
“…Because inertial and aerodynamic power requirements both scale with frequency cubed [24], increasing wbf by 16% would increase mechanical power requirements by over 55%. Spring-like structures in the insect flight system have a finite capacity for elastic energy exchange [6], therefore the musculature would have to supply this increased power demand. Under tethered in vivo conditions, Manduca sexta power muscles produce only 50% of peak power and this power can be modulated with precise timing [41,2].…”
Section: Manduca Sexta Utilizes Substantial Wingbeat Frequency Modulamentioning
confidence: 99%
See 2 more Smart Citations
“…Inertial power is often not considered as a cost, because it is assumed that minimal power is required for the inertial acceleration of the wings due to energy storage and return. However, it has been shown that the inertial power, while significantly reduced, is not perfectly compensated by elastic elements (Gau et al 2019). Thus, the amplitude-based strategy of M. stellatarum should be beneficial from an inertial power point of view, and equally good as far as aerodynamic power is concerned.…”
Section: The High Wing Beat Frequency Of M Stellatarum Might Requirementioning
confidence: 99%